2014
DOI: 10.1186/1756-0500-7-501
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization of IL32 in basal-like/triple negative compared to other types of breast cell lines and tissues

Abstract: BackgroundTriple negative breast cancer (TNBC) and often basal-like cancers are defined as negative for estrogen receptor, progesterone receptor and Her2 gene expression. Over the past few years an incredible amount of data has been generated defining the molecular characteristics of both cancers. The aim of these studies is to better understand the cancers and identify genes and molecular pathways that might be useful as targeted therapies. In an attempt to contribute to the understanding of basal-like/TNBC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(34 reference statements)
2
8
0
Order By: Relevance
“…Based on their differential expression in the breast cell lines, the primer sets are ranked as primer set 1>primer set 5>primer set 2>primer set 4>primer set 3. Overall, the PCR analysis and densitometer readings validate what we observed in the cell lines and patient samples (Player et al, 2014), in that IL32 is differentially expressed in the cell lines and even though their levels vary, several transcript variants contribute to the differential pattern of expression observed in these samples.…”
Section: ------------------------------------------------------------supporting
confidence: 80%
See 2 more Smart Citations
“…Based on their differential expression in the breast cell lines, the primer sets are ranked as primer set 1>primer set 5>primer set 2>primer set 4>primer set 3. Overall, the PCR analysis and densitometer readings validate what we observed in the cell lines and patient samples (Player et al, 2014), in that IL32 is differentially expressed in the cell lines and even though their levels vary, several transcript variants contribute to the differential pattern of expression observed in these samples.…”
Section: ------------------------------------------------------------supporting
confidence: 80%
“…Park et al (2013) found that over expression of IL32β correlated with tumor progression in breast cells, however, compared to other tissues, less is known about IL32 in breast samples. Although their study show that luminal and TNBC cell types express IL32 gene, studies in our laboratory demonstrate substantial differential gene expression of IL32 in basal-like/TNBCs compared to normal and luminal breast cancer cell lines and patient samples (Player et al, 2014). Since our initial observations, we have performed studies to better characterize the IL32 gene in breast cancers.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…IL‐32β is a pro‐inflammatory cytokine that induces secretion of TNF‐α and IL‐6 by monocytes and macrophages . Immunohistochemical (IHC) analysis of primary BC samples showed that the expression of IL‐32β positively correlated with tumor size, number of lymph nodes, metastases and tumor stage .…”
Section: Activation Of Stat3 Through Secretion Of Cytokinesmentioning
confidence: 99%
“…An outline of our approach is given in Table1. As summary, we previously retrieved TNBC DNA microarray datasets from Gene Expression Omnibus and found thatIL32 cytokine was differentially expressed in some, not all TNBC cell lines and patient samples (18). Cytokines are immune-modulating proteins involved in both immune and epithelial cell signaling events.…”
Section: Brief Summary Of Experimental Approach Utilized In Investigamentioning
confidence: 99%